FEATURES OF IMPLEMENTING THE OPEN BANKING SYSTEM IN UKRAINE - Tyshchenko, Volodymyr; Tyshchenko, Olena (Current Problems of Sustainable Development, 2026)
The full-scale war in Ukraine has significantly altered approaches to customer service and prompted the widespread use of remote channels. In these circumstances, it is remote banking systems that ensure the continuity of financial services, public access to their own funds, and the ability to make payments, transfers and carry out other banking transactions, regardless of the customer’s location. In examining the origins of remote banking services in Ukraine, it has been established that the current stage of development is characterised by the introduction of Open Banking. An analysis of international experience indicates a rapid rise in customer demand for such systems. This paper provides a description of the main participants in the Open Banking system, whose interaction will ensure the functioning of the digital payment ecosystem and the implementation of mechanisms for exchanging financial data via API interfaces. The main participants include: account servicing payment service providers, third-party payment service providers and payment service technology operators. A study of European experience in implementing open banking technology has once again demonstrated that Ukraine’s banking system is gradually becoming an integral part of the European financial sector. This is also confirmed by the adoption of a number of important regulatory documents (the Law of Ukraine ‘On Payment Services’ and the ‘Regulations on Open Banking in Ukraine’), which ensure the implementation of the provisions of the EU’s ‘PSD2’ Directive into national legislation. The study identified the leading players in the domestic banking system in the field of open banking: PUMB, Pivdenny Bank and OTP Bank. Particular attention was paid to examining the benefits and risks of implementing Open Banking in Ukraine. The advantages highlighted included: improved convenience for customers, the potential to expand access to financial services, increased competition between banks, and greater transparency in financial transactions. At the same time, the challenges of the open banking system included: cybersecurity and data breach risks, dependence on digital technologies, the complexity of integration for banks, and issues regarding the protection of customers’ personal data. It was also noted that the further development of open banking in Ukraine is directly linked to the introduction of an instant payment system, which will speed up financial transactions, improve the user experience of services and create new digital payment solutions.